Psychosomatic Medicine An International Primer for the Primary Care Setting - Fritzsche, Kurt; McDaniel, Susan H.; Wirsching, Michael (Springer New York : Imprint: Springer, 2014)
Psychosocial problems appear within a medical context worldwide, and are a major burden to health. Psychosomatic Medicine: An International Primer for the Primary Care Setting takes a uniquely global approach in laying the foundations of biopsychosocial basic care (such as recognizing psychosocial and psychosomatic problems, basic counseling, and collaboration with mental health specialists) and provides relevant information about the most common mental and psychosomatic problems and disorders. The scope of the book is intercultural-it addresses global cultures, subcultures living in a single country, and strengthening the care given by physicians working abroad.   This clinically useful book outlines best practices for diagnosing the most common biopsychosocial problems and mastering the most common communication challenges (e.g. doctor-patient conversation, breaking bad news, dealing with difficult patients, family and health systems communication and collaboration). Every chapter integrates basic theoretical background and practical skills and includes trans-culturally sensitive material, important for work with patients from different cultures. Psychosomatic Medicine: An International Primer for the Primary Care Setting serves as an excellent resource for clinicians hoping to gain and develop knowledge and skills in psychosomatic medicine.